Morphological diagnosis of a new species in Myrcia sensu lato (Myrtaceae) from Bahia, Brazil, with molecular highlights - Staggemeier, Vanessa Graziele; Lucas, Eve (Phytotaxa, 2014)
Myrcia marianae, a new species endemic from southern Bahia is described and compared to the related species Marlierea sucrei and Marlierea glabra using molecular and morphological analyses.